THE EFFECT OF TIKTOK VIDEO IN LEARNING PRONUNCIATION SKILL - Dhea, Dhea Aprilia Nasution; , Nurlaili (Journal of English Language and Literature Teaching, 2023)
The purpose of this research was to found out the effect of Tiktok video in learning pronunciation skill at grade tenth of SMA Negeri 2 Lubuk Pakam. The sample of this research was 50 students took from the tenth grade of SMA Negeri 2 Lubuk Pakam, consisting of 25 students as an experimental class using Tiktok video as media and 25 students as a control class without Tiktok video. The method used in this research is quantitative method. In collecting data, researchers conducted pre-test and post-test by giving a test consisted of 20 vocabulary items for each test. The results of this research showed that there is a significant difference in students' pronunciation by using Tiktok videos. This is evidenced by the average score of the pre-test of the experimental class was 43.6 and the post-test was 67.68. While the mean score of the control class pre-test was 37.76 and the post-test was 48.68. In addition, the results of data calculations show that at a significance level of 0.05, t-observed of 4.80 with t-table of 1.677, or 4.80 > 1.677. Therefore, it can be concluded that learning pronunciation using Tiktok videos is effective.